Effects of sodium hydroxide and sodium silicate solutions on compressive and shear bond strengths of FA–GBFS geopolymer. (30th August 2015) - Phoo-ngernkham, Tanakorn; Maegawa, Akihiro; Mishima, Naoki; Hatanaka, Shigemitsu; Chindaprasirt, Prinya
Highlights: FA–GBFS geopolymer activated with sodium silicate (cured at 23 °C) resulted mainly in amorphous gel. Activated with sodium hydroxide resulted in significant crystalline CSH. Incorporation of GBFS enhanced compressive strength and microstructure of FA geopolymer pastes. Shear bond strength depended on strength and amount of NASH gel of FA–GBFS geopolymer. Abstract: This article investigated the effects of sodium hydroxide and sodium silicate solutions on the properties of fly ash (FA)–granulated blast furnace slag (GBFS) geopolymer. Three types of geopolymer pastes viz., FA paste, FA + GGBS paste and GGBS paste were tested. They were activated with three types of alkaline solutions viz., sodium hydroxide solution (NH), sodium silicate solution (NS), and sodium hydroxide plus sodium silicate solution (NHNS). NH with 10 molar concentration, alkaline liquid/binder ratio of 0.60 and curing at ambient temperature of 23 °C were used for all mixes. The results indicated that the reaction products and strengths of geopolymer depended on the types of source materials and alkali activators. The use of NH and NHNS solutions resulted in the formation of crystalline calcium silicate hydrate (CSH) which co-existed with amorphous gel. Whereas the use of NS solution resulted in mainly the amorphous products with only a small amount of crystalline CSH in GBFS paste. The increase in GBFS content enhanced the compressive strength and microstructure of geopolymer pastes due to the formation of additional CSH. The shear bond strength between Portland cement concrete substrate and geopolymer paste was found to relate to both compressive strength and amount of NASH gel of geopolymer paste.